Sunlight and SARS-CoV-2: can sunlight and UV exposure mitigate the propagation of COVID-19? - Leclézio, Alexandra; Robinson, Jared; Banerjee, Indrajit (Journal of Chitwan Medical College, 2021)
Background: This review aims to assess the contributing role of sunlight on mitigating the propagation of COVID-19, and to assess how sunlight as well as artificial UV light may be a natural, more cost effective and eco-friendly method of disinfection which can be implemented in order to help to combat this rampant pandemic.Methods: An extensive literature survey of English literature was conducted using Pubmed, Pubmed Central, Medline, Google Scholar and WHO Nepal Situation Updates on COVID-19. A combination of keywords was entered: “Sunlight” OR “Disinfection”; OR “Ultraviolet Rays”; OR “SARS-CoV-2”; OR “Coronavirus Disease 2019”; OR “COVID 19”; AND ‘Nepal’.Results: Sunlight is composed of UVA (95%) and UVB (5%) radiation, UVB is most effective to inactivate SARS-CoV-2 and does so by damaging the RNA genome of the virus, and increasing levels of reactive oxygen species in the air. SARS-CoV-2 is nullified by a UVB flux of 28 J/m2, and needs to be exposed for a sufficient duration depending on the time of day, season, geographic location or the specific locality, in order to be inactivated.Conclusion: Developing countries could benefit from taking advantage of using sunlight as a cost-free and environmentally friendly method of disinfection. It is imperative that all countries capitalize on this method of disinfection, it is cost-free, easy and therefore can be implemented on a large scale with relative ease.